Expanding the vision of faculty learning communities in higher education : emerging opportunities for faculty to engage each other in learning, teaching and support - Rainville, Kristin N.; Title, David G.; Desrochers, Cynthia G. (Transforming teaching and learning in higher education (Charlotte, N.C.), 2024)
"This edited book on Faculty Learning Communities (FLCs) explores the ways in which FLCs have expanded across platforms, spaces, and focus while maintaining the core values and elements of original FLCs. The first section investigates ways that FLCs support faculty retention, teaching and scholarship. The second section offers examples of FLCs focused on teaching that is responsive to student learning. The third section explores the move to online and virtual FLCs. The fourth section explores FLCs that create and foster faculty belonging, communities of care, and integrate mindfulness. The fifth section looks at multi-year, long term progression and impact of FLCs. The book's foreword, by Milton D. Cox, investigates the evolution of leadership of and within faculty learning communities as they expand"--